المنظم الاقتصادي وريادة التنمية الصناعية ( مع التركيز على تجربة الاستثمار الصناعي الخاص في العراق) (Al-Mansour Journal, 2023)
المنظم الاقتصادي وريادة التنمية الصناعية ( مع التركيز على تجربة الاستثمار الصناعي الخاص في العراق)